Premenstrual Dysphoric Disorder: Ranking the Symptoms and Severity in Indian College Students. Issue 2 (April 2019) - Bansal, Deepali; Raman, Rajesh; Rao, T. S. Sathyanarayana
Abstract: Background: Premenstrual syndrome (PMS) and premenstrual dysphoric disorder (PMDD) are common conditions causing significant impairment in various domains of life. Both the conditions are associated with physical, emotional, and behavioral symptoms. There is dearth of studies regarding symptomatology and severity of the condition in Indian college students. Aim: Aim of this study is to categorize and rank the symptoms and severity of PMDD in college students in India. Materials and methods: A cross-sectional survey was conducted in various colleges of Mysuru. A total of 600 girls were approached over a period of 1 year. Confidentiality was assured and written informed consent was taken. Girls with irregular periods and those who had an absence of menstruation since last 3 consecutive menstrual cycles were excluded. A total of 571 filled up forms were taken for analysis. Data was analyzed using SPSS 22 version software. Chi-square test was used as the test of significance for qualitative data. Results: The mean age of participants was 21.12 ± 2.6 years. Majority of the subjects were unmarried and were from urban background. The prevalence of PMS/PMDD was 46.1%, out of which 10.2% met the criteria for PMDD. Physical symptoms (91.4%) were the most commonly reported symptom domain in the PMDD category, followed by anger or irritability (84.5%). Almost half of the subjects with no or mild PMS had reported physical symptoms. The least reported symptom was insomnia. PMDD group had reported maximum impairment in the domain of relationship with family members (77.6%), followed by home responsibilities and relationship with coworkers. Conclusion: This study suggests that the prevalence of clinically relevant PMS/PMDD is higher than widely cited estimates and is a cause of concern for health care authorities in India. Physical complaints are the most commonly reported among all the symptoms in all groups. There is a need to actively assess for premenstrual symptoms in young women for comprehensive treatment and good outcome.